Delirium in a surgical context from a nursing perspective: A hybrid concept analysis - Poikajärvi Satu; Rauta Satu; Salanterä Sanna; Junttila Kristiina (Elsevier B.V., 2022)
Background
The term delirium has been defined in medical diagnosis criteria as a multidimensional disorder, and the term acute confusion is included in nursing classifications. Delirium can be a serious complication assessed in a patient after a surgical procedure. Still, the patient's delirium frequently remains unrecognised. Care of patients with delirium after surgical procedure is complex, and it challenges nursing expertise. From the nurses’ viewpoint, delirium is associated with ambiguity of concepts and lack of knowledge. Therefore, reseach on how nurses perceive patients with delirium in a surgical context is needed.
Objective
The aim of this study was to describe the concepts of delirium and acute confusion, as well as the associated dimensions, in adult patients in a surgical context from the nursing perspective.
Design
The study used Schwartz and Barcott's hybrid concept analysis with theoretical, fieldwork, and final analytical phases.
Settings
Surgical wards, surgical intensive care units, and post-anaesthesia care units.
Data sources
A systematic literature search was performed through Pubmed (Medline), Cinahl, PsycInfo, and Embase.
Participants
Registered nurses and licensed practical nurses (n = 105) participated in the fieldwork phase.
Methods
In the theoretical phase, the concepts’ working definitions were formulated based on a systematic literature search with the year limitations from 2000 until February 2021. At the fieldwork phase, the nurses’ descriptions of patients with delirium were analysed using the deductive content analysis method. At the final analytical phase, findings were combined and reported.
Results
The concepts of delirium, subsyndromal delirium, and acute confusion are well defined in the literature. From the perspective of the nurses in the study, concepts were seen as a continuum not as individual diagnoses. Nurses described the continuum of delirium as a process with acute onset, duration, and recovery with the associated dimensions of symptoms, symptom severity, risk factors, and early signs. The acute phase of delirium was emphasised, and preoperative or prolonged disturbance did not seem to be relevant in the surgical care context. Patients’ compliance with care may be decreased with the continuum of delirium, which might challenge both patients’ recovery from surgery and the quality of nursing care.
Conclusions
In clinical practice the nurses used term confusion inaccurately. The term acute confusion might be used when illustrating an early stage of delirium. Nurses could benefit from further education where the theoretical knowledge is combined with the clinical practice. The discussion about the delirium, which covers the time both before surgery and after the acute phase should be increased.